Fabrication & performance study of a palladium on alumina supported membrane reactor: Natural gas steam reforming, a case study. (12th April 2018) - Anzelmo, B.; Liguori, S.; Mardilovich, I.; Iulianelli, A.; Ma, Y.-H.; Wilcox, J.; Basile, A.
Abstract: In this work, a synthetic mixture of natural gas is considered in a steam reforming process for generating hydrogen by using a membrane reactor housing a composite membrane constituted of a Pd-layer (13 μm) supported on alumina. The Pd/Al2 O3 membrane separates part of the produced hydrogen through its selective permeation, although it shows a relatively low H2 /N2 ideal selectivity (>200 at 0.5 bar of trans-membrane pressure and T = 425 °C). The steam reforming reaction is performed at 420 °C, by varying the gas hourly space velocity between 4400 h −1 and 6900 h −1 and by using two different mixtures containing some common impurities found within natural gas pipeline. Specifically, the effect of N2 and CO2 as impurities in the feed line is analyzed. The reaction pressure and steam-to-carbon ratio (S/C) are kept constant at 3.0 bar (abs.) and 3.5/1, respectively. The best performance of the Pd-based membrane reactor is obtained at 420 °C, 3.0 bar and 100 mL/min of sweep-gas, yielding a methane conversion of 55% and hydrogen recovery >90%. Highlights: Natural gas steam reforming was performed at 420 °C in a Pd/Al2 O3 membrane reactor. The Pd/Al2 O3 membrane reactor recovered around 90% of H2 at 420 °C and 3.0 bar. The Pd/Al2 O3 membrane reactor yielded around 55% of CH4 conversion at 420 °C and 3.0 bar.